Ontogeny of the Osmoregulatory Capacity of Teleosts and the Role of Ionocytes - Fridman, Sophie (Frontiers in Marine Science, 2020)
Whilst osmoregulation in the adult teleost fish has been extensively studied and significant advances have been made in recent years, much less information exists regarding osmoregulation during the early stages of development of teleosts. Adult fish maintain their blood osmolality in a narrow physiological range, i.e. ≈ 280 - 360 mOsm kg-1, through the combined osmoregulatory capabilities of several sites i.e. branchial chambers, skin, digestive system and urinary organs. However embryonic and post-embryonic stages maintain their blood osmolality in a less narrow range of ≈ 240 - 540 mOsmol kg-1 and osmoregulatory capacity is restricted to the cutaneous ionocytes located on the tegument with a transference in osmoregulatory function occurring during the early life stages to the developing digestive tract, the urinary organs and the developing branchial tissues and the ionocytes which they support. This review will discuss the development of osmoregulatory capacity that occurs throughout early life stages of teleosts and its role in conserving physiological homeostasis, focusing on the form and function of related mechanisms, i.e. the ionoregulatory cell or ionocyte, outlining the different roles and functions of different ionocyte types relative to their environment, i.e. freshwater or seawater, their plasticity and discuss spatio-temporal changes in ionocyte distribution that occur during ontogeny.